Analysis of Vowel Pronunciation Errors of Grade IX Students of MTs Harapan Jasa Langkat - Annisa Sevia Putri; Melinda Nata Sari; Rizka Dwi Fani; Sylfana Ryan Mulia; Supriadi (Journal of Applied Linguistics, 2023)
This research aims to observe pronunciation errors and vowels of Grade IX students of MTs Harapan Jasa Makmur. Based on the observation, the writer noted that the students had difficulty differentiating English vowels. The type of this research was a qualitative method, which is descriptive and tends to use analysis and it was in the form of words instead of numbers. In this study, the main data collection techniques were participant observation, in-depth interviews, documentation studies, and a combination of the three or triangulation. The author chose class IX containing 7 students to be sampled in his research. The authors ran several tests that they spoke and recorded each word. after our research, it turns out that there were still many students who can't pronounce English enough. Around 50% of students are lacking in English pronunciation and the teacher's solution was by giving repetition and repeating the material that has been studied, especially English pronunciation. Key Words: Vowel Sound, Pronunciation Errors